Fabricating Ag/PW12/Zr‐mTiO2 Composite via Doping and Interface Engineering: An Efficient Catalyst with Bifunctionality in Photo‐ and Electro‐Driven Nitrogen Reduction Reactions. (20th October 2021) - Feng, Caiting; Liu, Jiquan; Li, Qinlong; Ji, Lei; Wu, Panfeng; Yuan, Xiaoxiao; Hu, Huaiming; Jiang, Hai‐Ying; Xue, Ganglin
Abstract: Driven by solar power and derived electricity, ambient photo‐ and electrochemical nitrogen fixations are considered promising strategies to produce low‐concentration NH3 /NH4 + . Under the principles of doping and interface engineering, a Ag/PW12 /Zr‐ m TiO2 composite is fabricated in a one‐pot synthesis, where zirconium‐doped mesoporous TiO2 is co‐decorated with silver nanoparticles (Ag NPs, optimal 1 wt%) and phosphotungstic acid (PW12, optimal 10 wt%). Enhanced nitrogen chemisorption is achieved owing to Zr‐doping, where the mesoporous structure of Zr‐ m TiO2 favors nitrogen mass transfer. Ag NPs decoration leads to visible light absorption. At the interface, PW12 and Ag NPs decelerate the recombination of photo‐generated charge carriers. A Z‐scheme mechanism is suggested for the hetero‐junction, and the surface plasmon resonance effect of Ag NPs is considered in the composite. Consequently, a NH3 /NH4 + production rate of 324.2 µ mol gcat −1  h −1 is achieved in the photo‐driven process, together with the structure‐reactivity relationship between transient photocurrent intensity and catalytic efficiency. Moreover, constructing Ag/PW12 /Zr‐ m TiO2 heterojunction introduces a plentitude of active sites for the electrochemical process, together with enhanced charge transfer efficiency at the interface. Hence, an excellent NH3 /NH4 + production rate of 55.0 µ g mgcat −1 h −1 is accomplished at −0.6 V vs RHE. The robustness and superior activity of Ag/PW12 /Zr‐ m TiO2 in both photo‐ and electro‐driven processes may offer an opportunity for effectively utilizing sunlight. Abstract : Doping and interface engineering are incorporated in fabricating a Ag/PW12 /Zr‐ m TiO2 composite with bi‐functionality. In a photochemical process, a NH3 /NH4 + production rate of 324.2 μmol gcat −1 h −1 is accomplished. In addition to the surface plasmon resonance effect of Ag nanoparticles, a Z‐scheme mechanism is proposed between Zr‐ m TiO2 and PW12 . In an electrochemical process, superior NH3 /NH4 + production rate of 55.0 μg mgcat −1 h −1 is achieved at −0.6 V vs RHE.